2015
DOI: 10.9738/intsurg-d-13-00242.1
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Pancreatic Pseudocyst Radiologically Mimicking Gastrointestinal Stromal Tumor

Abstract: Heterotopic pancreas is a relatively common variant of foregut embryologic dystopia that can be described as pancreatic tissue found outside the normal anatomic location, being independent from vascular supply of normal pancreas. Having all features of pancreatic tissue except for the major duct structures, this ectopic tissue may be clinically recognized when pathologic changes take place. Inflammation, hemorrhagic or obstructive states, and eventually malignancy-related problems may become a diagnostic chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In the stomach, heterotopic pancreas may resemble gastrointestinal stromal tumors, the most prevalent submucosal gastric lesions. 5 , 6 This similarity lies not only in the shared physical appearance but also the fact that both masses are found in the submucosal layer. 6 This difficulty in correctly distinguishing between pancreatic heterotopia and a tumor has been noted to persist even with the use of advanced imaging techniques.…”
Section: Discussionmentioning
confidence: 88%
“…In the stomach, heterotopic pancreas may resemble gastrointestinal stromal tumors, the most prevalent submucosal gastric lesions. 5 , 6 This similarity lies not only in the shared physical appearance but also the fact that both masses are found in the submucosal layer. 6 This difficulty in correctly distinguishing between pancreatic heterotopia and a tumor has been noted to persist even with the use of advanced imaging techniques.…”
Section: Discussionmentioning
confidence: 88%
“…Manifestations of acute and chronic pancreatitis in HP tissues were the second most common presentation in our review. Clinical symptoms may include abdominal pain, nausea, vomiting, anorexia and weight loss[ 85 , 163 ]. Similar to orthotopic pancreatitis, the most common causes can be related to alcohol, medications, smoking, autoimmune disease or inadequate ductal drainage[ 243 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions that are small and otherwise asymptomatic for decades, may also become acutely symptomatic in setting of inflammation and edema[ 60 , 92 ]. Likewise, the development of cysts and fluid collections within the wall of the stomach may grow to a size that can impede gastric emptying[ 163 ]. Some have also proposed that HP lesions may cause functional obstruction due to pyloric spasm[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histological analysis showed that numerous acini, few ducts and some endocrine islets were found in the submucosa, muscularis propria and serosa; thus, a type I lesion was considered according to the Heinrich and Gaspar-Fuentes classification. Previous studies have reported that cystic changes can be seen in EP tissue and that retention cysts are usually small (less than 1–2 cm in size) and lined by a single layer of normal pancreatic epithelium, whereas pseudocysts are usually larger with walls that lack an epithelial lining [ 13 , 14 ]. Furthermore, pancreatic cysts are classified as neoplastic or nonneoplastic.…”
Section: Discussionmentioning
confidence: 99%